Use of a blast coating process to promote adhesion between aluminium surfaces for the automotive industry. Issue 6 (25th April 2020) - Flanagan, Joe; Schütze, Paul; Dunne, Conor; Twomey, Barry; Stanton, Kenneth T.
ABSTRACT: The influence of surface roughness on adhesive bond strength for aluminium to aluminium bonding is investigated. firstly, the effect of varying surface roughness is investigated using grit-blast surface preparation. this is then compared to a novel ambient temperature blast coating technique known as coblast which, using a co-incident blast stream of abrasive and coating media, simultaneously removes a surface's native passivation layer while depositing an active epoxy primer coating on the newly-exposed reactive metal surface. a range of al2 o3 abrasive media with particle sizes from < 13 μ m to < 1200 μ m were used to prepare the varying surface roughness profiles. characterisation techniques such as surface profilometry, sem, edx, x-ray diffraction and light microscopy were used to investigate the level of coating coverage along with the degree of plastic deformation induced in the substrate as a result of the coating procedure. in addition, a modified lap shear test was conducted along with salt fog corrosion testing. results indicate that replacement of the grit-blast treatment with the epoxy coblast coating gives cohesive failure and an increase in lap shear strength of up to 15% before corrosion testing and up to 36% after 240 hours in a salt fog chamber.